Cytogenetic studies on newborns from high and normal level natural radiation areas of Kerala in southwest coast of India. (April 2013) - Ramachandran, E. N.; Karuppasamy, C. V.; Cheriyan, V. D.; Soren, D. C.; Das, Birajalaxmi; Anilkumar, V.; Koya, P. K. M.; Seshadri, M.
Abstract Purpose: To study, characterize and compare chromosome aberrations and karyotype anomalies among newborns from high (> 1.5 mGy/y) and normal (≤ 1.5 mGy/y) level natural radiation areas of monazite-sand bearing southwest coast of Kerala in India. Materials and methods: Cord blood samples from newborns were collected from selected Government hospitals in heparinized vials and cultures were set up employing standard microculture techniques, slides were prepared, coded and stained with giemsa. Well spread metaphases were analyzed for chromosome aberrations and karyotype anomalies. Results: A total of 1, 267, 788 metaphases from 27, 295 newborns of mothers aged 17–45 years (17, 298 from high and 9, 997 from normal level radiation areas) were analyzed during 1986–2007. Frequencies of dicentrics in high and normal level radiation areas were 1.90 ± 0.14 and 2.01 ± 0.26 per 10, 000 cells, respectively (Relative frequency [RF] = 0.94; 95% CI: 0.71–1.26). Karyotype anomalies had a frequency of 5.49‰ and 6.7‰, respectively (RF = 0.82; 95% CI: 0.60–1.12). No dose-related trend was observed in chromosome aberrations or karyotype anomalies. Conclusion: Frequencies of chromosomal aberration and karyotype anomalies between the newborns from the high level natural radiation area (HLNRA) and normal level natural radiation areas (NLNRA) were very similar.